Danos e comportamento larval de helicoverpa armigera (hübner) (lepidoptera: noctuidae) em soja - Stürmer, Glauber Renato (2016)
In order to have a greater knowledge and hence greater control of the insect pest in study, this research was developed into two articles. In the first article, damage infestation of 2, 4 and 6 caterpillars/m² at different growth stages and the impact on soybean grain yield components were evaluated. The experiments were carried out in the growing seasons of 2013/14 and 2014/15, in Santa Maria/RS. The soybean cultivar BMX Potência RR was sown in 0.5 m spaced rows, with density of 18 plants m-2. The H. armigera larvae utilized were in third instar and obtained from artificial production. The experimental units consisted of screened cages of 1m x 1m x 1m, placed on soybeans only during the evaluation period, containing 18 soybean plants. The treatments were densities of 2, 4 and 6 caterpillars/m² (cage), besides a control treatment without caterpillars. The period of coexistence of the caterpillars with plants was 15 days, with densities checked daily to maintain the correct number of caterpillars. In the reproductive stage, R5.3 was the most affected by the caterpillar damage. Greater H. armigera populations/m² cause increased number of damaged pods with two and/or three perforations per pod. The level of one caterpillar m² causes a reduction in grain yield in the order of 104.40, 266.42, and 374.69 kg ha-1 when infests soybeans in V3, R3 and R5.3 stage, respectively. In the second article, the behavior of caterpillars on infested soybean plants in growing stages was evaluated. The experiments were performed in the growing seasons of 2013/14 and 2014/15, in Santa Maria/RS. The experimental units were formed by iron cages covered by voile fabric type containing nine soybean plants, placed on crop only during the evaluation period. Soybean plants were infested with 20 caterpillars of 3rd instar in the V7, R2, and R4 stage. At each stage, the behavioral assessments of the caterpillars were performed every three hours over two days (48 hours), recording the activities of the 20 caterpillars. Assessments were performed visually by observing the following parameters: position occupied by the caterpillar in the plant, caterpillar activity, and the plant structure occupied by the caterpillar. H. armigera was found in the adaxial leaves of the upper third of soybean plant in the vegetative stage. In the reproductive stage, the caterpillars were distributed in the middle and upper third of the plants and located in the plant reproductive structures. The timetables of the day (temperature and humidity) influence on the caterpillar feeding and alter the caterpillar distribution in the thirds of the plant.